STRATIGRAPHIC MODEL OF THE GUA MUSANG FORMATION (MIDDLE PERMIAN-MIDDLE TRIASSIC), CENTRAL BELT OF PENINSULAR MALAYSIA - BIN ISMAIL, NORHISHAM (Universiti Teknologi PETRONAS, 2015)
The Gua Musang Formation can be classified into Middle Permian-Middle Triassic sediment comprising crystalline limestone and occurrence of interbedded thin beds of shale, tuff, chert nodules and subordinate sandstone. Three outcrops of the Gua Musang Formation have been studied where the stratigraphic model of the Gua Musang Formation were created including burial history and geothermic model. The first outcrop consist of sandstone and conglomerate, while the second outcrop consist of limestone and the third outcrop consists of shale and siltstone. From the model, the porosity of sandstone and silt was considered as moderate to good which can be an analogue to the reservoir of an effective petroleum system. The maximum temperate that had been exposed to the Gua Musang Formation ranging from 130⁰C-140⁰C which the process of katagenesis had taken place. Knowing the temperature structure, the knowledge and study in basin analysis of the Gua Musang Formation can be enhance. The knowledge regarding the stratigraphic and burial history of the formation will enhanced the knowledge of some petroleum system element in this portion of studied area.